Spatial Presence, Performance, and Behavior between Real, Remote, and Virtual Immersive Environments - Khenak, Nawel; Vezien, Jeanne; Bourdot, Patrick (IEEE transactions on visualization and computer graphics, 2020)
Spatial presence encompasses the user's ability to experience a sense of " being there ". While particular attention was given to assess spatial presence in real and virtual environments, few have been interested in measuring it in telepresence situations. To bridge this gap, the present work introduces a study that compares the execution of a task in three conditions: a real physical environment, a remote environment via a telepresence system, and a virtual simulation of the real environment. Following a within-subject design, 27 participants performed a navigation task consisting in following a route while avoiding obstacles. Spatial presence and five related factors (affordance, enjoyment, attention allocation, reality, and cybersickness) were evaluated using a presence questionnaire. In addition, performance measures were gathered regarding environment recollection and task execution. The evaluation also included a behavioral metric measured by obstacle avoidance distance extracted from participants' trajectories. Results indicated a higher presence in the real environment, along with the best performance measures. No difference was found in spatial presence between the remote and the virtual conditions, although a higher degree of affordance and enjoyment was attributed to the virtual environment, and a higher degree of reality was attributed to the remote environment. The number of collisions was found to be lower in the remote condition compared to the virtual condition. Similarly, the avoidance distance was also bigger (and almost similar) in the real and the remote environments compared to the virtual environment indicating a greater caution of participants. These cues highlight that the behavior of participants in the remote condition was closer to their behavior in the real situation than it was in the virtual condition. Furthermore, positive correlations were found between the reality factor and two of the three performance measures, as well as with the behavioral metric. This suggests that the degree of physical existence of the space in which participants operate can influence their performance and behavior.